Instabilities of proteins: theoretical aspects, degradation products and methods for their detection - Suzana Trajkovic-Jolevska; Jasmina Tonic-Ribarska; Aneta Dimitrovska (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2005)
Recombinant DNA technology has led to a significant increase in the number of peptide and protein based pharmaceuticals, giving a new approach to combat poorly controlled diseases. This particular development has been reached in the last two decades. However, proteins are highly susceptible of physical and chemical degradation resulting in a decrease or complete loss of biological activities. Reasons for their physical and chemical instabilities and the methods for their examination, become a challenge for the pharmaceutical scientists for successful development of stabile protein - based pharmaceuticals. The stability of protein - based pharmaceuticals is significant in terms of their pharmaceutical quality and biological activity. In addition, a right choice of suitable analytical methods is needed in order to detect an early formation of degradation products or modified forms.